Опыт комплексного лечения синдрома диабетической стопы - Супрун, Е.В.; Чуков, А.Б.; Мищенко, С.В.; Супрун, Н.В. (Актуальні проблеми транспортної медицини, 2005)
In the work presented they describe the experience of 28 diabetic foot patients treatment. In the curative scheme offered they used successfully prostaglandin E1 and alfa-lipoic acid. Its high clinical efficacy is demonstrated.